The δ-Opioid Receptor Differentially Regulates MAPKs and Anti-inflammatory Cytokines in Rat Kidney Epithelial Cells Under Hypoxia - Luo, Fengbao; Xu, Renfang; Song, Guanglai; Lu, Hao; He, Xiaozhou; Xia, Ying (Frontiers in Physiology, 2020)
Hypoxic injury is one of the most important factors in progressive kidney disorders. Since we have found that δ-opioid receptor (DOR) is neuroprotective against hypoxic stress through a differential regulation of mitogen-activated protein kinases (MAPKs) and anti-inflammatory cytokines, we asked if DOR that is highly expressed in the kidney can modulate renal MAPKs and anti-inflammatory cytokines under hypoxia. We exposed cultured rat kidney epithelial cells (NRK-52E) to prolonged hypoxia (1% O2) with applications of specific DOR agonist or/and antagonist to examine if DOR affects hypoxia-induced changes in MAPKs and anti-inflammatory cytokines. The results showed that endogenous DOR expression remained unchanged under hypoxia, while DOR activation with UFP-512 (a specific DOR agonist) reversed the hypoxia-induced up-regulation of ERK1/2 and p38 phosphorylation. DOR inhibition with naltrindole had no appreciable effect on the hypoxia-induced changes in ERK1/2 phosphorylation, but increased p38 phosphorylation. DOR inhibition with naltrindole attenuated the effects of DOR activation on the changes in ERK1/2 and p38 phosphorylation in hypoxia. Moreover, DOR activation/inhibition differentially affected the expression of transcriptional repressor B-cell lymphoma 6 (Bcl-6), anti-inflammatory cytokines tristetraprolin (TTP) and interleukin-10 (IL-10). Taken together, our novel data suggest that DOR activation differentially regulates ERK1/2, p38, Bcl-6, TTP and IL-10 in the renal cells under hypoxia.